2008
DOI: 10.1007/s00125-008-1184-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimal dose of lisinopril for renoprotection in type 1 diabetic patients with diabetic nephropathy: a randomised crossover trial

Abstract: Aims/hypothesis The purpose of this study was to evaluate the optimal renoprotective effect of ultrahigh doses of lisinopril, as reflected by short-term changes in urinary albumin excretion rate (UAER), in type 1 diabetic patients with diabetic nephropathy. Methods At the Steno Diabetes Center, 49 type 1 diabetic patients with diabetic nephropathy completed this doublemasked randomised crossover trial consisting of an initial washout period followed by three treatment periods each lasting 2 months, where all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 9 publications
1
15
0
3
Order By: Relevance
“…Dosing of antiproteinuric RAAS blockade was recently discussed [8] and has so far been investigated in a fraction of the treatments used today [3,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosing of antiproteinuric RAAS blockade was recently discussed [8] and has so far been investigated in a fraction of the treatments used today [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…The trials used antihypertensive doses not necessarily optimal for renoprotection. Several dosage studies [3,4] have demonstrated dosedependent antiproteinuric effects. After the introduction of the renin inhibitor aliskiren and evidence of its antiproteinuric effects [2,5] we aimed to investigate the antiproteinuric effect of increasing doses of aliskiren, by comparing urinary albumin excretion rate (UAER) during placebo and after 2 months of treatment with aliskiren 150 mg, 300 mg or 600 mg once daily.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, 13 in a single centre, double-blind, randomized cross-over trial, 49 patients with type 1 diabetes and nephropathy received three treatment periods with 20, 40 or 60 mg/day of lisinopril. Each period lasted for 2 months.…”
Section: Does Higher Dose Of Acei or Arb Improve Proteinuria?mentioning
confidence: 99%
“…Es stellt sich immer wieder die Frage, ob möglicherweise höhere Dosen von ACE-Hemmern zusätzliche nephroprotektive Effekte haben. Diese Fragestellung wurde bei Patienten mit Typ-1-Diabetes, die an einer Nephropathie litten, für den ACE-Hemmer Lisinopril in einer randomisierten "Cross-over-Studie" untersucht [30]. Hierbei zeigte sich, dass Lisinopril 40 mg einmal täglich im Vergleich zu Lisinopril 20 mg einmal täglich zu einer zusätzlichen Reduktion des Blutdrucks sowie der Albuminurieausscheidung ohne Zunahme der Nebenwirkung führte [30].…”
Section: > Nephroprotektive Effekte Von Ace-hemmern Und At1-blockern unclassified